2020
DOI: 10.21608/svuijm.2020.123716
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of contributory role of inflammation in patients with knee osteoarthritis

Abstract: Osteoarthritis (OA) is a degenerative joint disease characterized by articular cartilage degradation which can affect many joints in the body, but is particularly common in weight-bearing joints such as the knee and hip. The loss of cartilage can lead to joint space narrowing (JSN), pain, and loss of function and ultimately leads to the need for total joint replacement. There are a number of risk factors associated with OA, including genetic predisposition, obesity, age, and previous joint trauma. With obesity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Hanada M, et al in their study (14), The ESR levels of individuals who had knee osteoarthritis were greater than the ESR levels of patients who did not have knee osteoarthritis. In the research that Zaki NA, et al conducted (16). The minimum ESR value was 20 mm/h, and the maximum one was 27 mm/h.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Hanada M, et al in their study (14), The ESR levels of individuals who had knee osteoarthritis were greater than the ESR levels of patients who did not have knee osteoarthritis. In the research that Zaki NA, et al conducted (16). The minimum ESR value was 20 mm/h, and the maximum one was 27 mm/h.…”
Section: Resultsmentioning
confidence: 95%
“…In a study on CRP, Zaki NA, et al (16). There is evidence that inflammation plays a contributing role in patients who have osteoarthritis of the knee.…”
Section: Resultsmentioning
confidence: 99%
“…We had demonstrated these findings in a previous work (Hassan et al 2021). In addition, Zaki et al confirmed the presence of inflammatory state among patients with KOA especially those with severe form (Zaki et al 2020). Cicuttini and Wluka suggested reclassifying OA as a systemic disease rather than a focal joint disease (Cicuttini and Wluka 2014).…”
Section: Discussionmentioning
confidence: 92%